(untitled) (Pedagogy of Higher and Secondary Education, 2006)
In article the theoretical and the practical aspects of the problem of the forming of pupils musical styles tn the condition of extra-curricular work are considered. Modern methods of their development and positive influence on the common culture of the growing generation are defined.